Phonetic Dialecticisms in the Novel «The Century of Jacob» by Volodymyr Lys and their Equivalents in the Zgorian Dialect: Comparative Aspect (Linguostylistic Studies, 2018)
Writers used dialects in their texts long time ago. In the 19th century Y. Golovatskyi, M. Shashkevych, I. Vagilevych, Yu. Fedkovych, I. Franko wrote their literary works using dialectical language. In the late 19th – early 20th century, V. Stefanyk, M. Cheremshyna, M. Kotsubynsky, O. Honchar used dialects stylizing their texts with rural speech. Ukrainian writers were interested in Polissian dialects in the late 80s of the 20th century. The novel “The Century of Jacob” by V. Lys was written in Zgorany dialect. The purpose of the article is to compare the dialectal language of the novel “The Century of Jacob” with the dialects spoken in Zgorany village, Lyubomlskyi district of Volyn region and to find out the relevance of the text to the folk language. We carried out an expedition to Zgorany village in summer of 2015. Phonetic dialecticisms of the novel “The Century of Jacob” can be divided into two groups. The first group includes dialecticisms that are similar both in the novel and the dialect spoken in the Zgorany area. The second group involves those dialecticisms which are different from them.As a result of the study, we have found out  that a part of the phonetic dialecticisms used by V. Lys in his novel “The Century of Jacob” are identical to the modern Zgorian dialect, but a  significant part of these dialecticisms are different.The study elucidates the reasons for this discrepancy. Firstly, this is an influence of the literary language on the dialect. Secondly, the writer uses abnormal forms for this dialect, for example, changing [а] > [е] in words trymaisie, vsilysie, na vorotiekh; softening the sibilant in the word shchistsia. Thirdly, the author doesn’t show the phonetic characteristic features of the dialect, for example, hardness of the sound [рꞌ]. Then V. Lys shows typical for Zgorany dialect phonetic characteristic in some words (chuluvik, kumediia, huvuryty, but bomaha). Moreover, the writer uses different forms of one word in the other words (for example, viina ǀǀ vuina, pushov ǀǀ puishov, zuvsim ǀǀ zusim etc.). V. Lys wanted to create the atmosphere of the Ukrainian village in his novel, so he wrote it in Zgorany dialect. For this purpose the writer sometimes adapted some words to the Zgorany dialect, although they have never been used in this dialect. As a result, the novel “The Century of Jacob” has become very popular and western Polissian dialect became very interesting for readers outside Volyn Polissya.
Keywords: phonetic dialect; Zgoran dialect; expedition; influence of literary language; vocalism; consonantism